2016
DOI: 10.1091/mbc.e15-04-0230
|View full text |Cite
|
Sign up to set email alerts
|

Sequential and compartmentalized action of Rabs, SNAREs, and MAL in the apical delivery of fusiform vesicles in urothelial umbrella cells

Abstract: As major urothelial differentiation products, uroplakins are targeted to the apical surface of umbrella cells. Via the sequential actions of Rabs 11, 8, and 27b and their effectors, uroplakin vesicles are transported to a subapical zone above a K20 network and fuse, via a SNARE-mediated and MAL-facilitated step, with the urothelial apical membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 81 publications
(131 reference statements)
4
43
1
Order By: Relevance
“…VAMP3 plays a role in endocytosis in various types of cells (McMahon et al, 1993), but VAMP3 KO mice develop normally. VAMP8 is also expressed in the bladder and is involved in the apical delivery of fusiform vesicles within the umbrella cells (Wankel et al, 2016). VAMP4 KO mice have not been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…VAMP3 plays a role in endocytosis in various types of cells (McMahon et al, 1993), but VAMP3 KO mice develop normally. VAMP8 is also expressed in the bladder and is involved in the apical delivery of fusiform vesicles within the umbrella cells (Wankel et al, 2016). VAMP4 KO mice have not been reported.…”
Section: Introductionmentioning
confidence: 98%
“…VAMP8 regulates the exocrine systems, and VAMP8 KO mice showed severe defects in the pancreas and kidney (Wang et al, 2004(Wang et al, , 2009. VAMP8 is also expressed in the bladder and is involved in the apical delivery of fusiform vesicles within the umbrella cells (Wankel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In umbrella cells, pairs of maturing plaques are assembled within discoidal vesicles, separated by inter-plaque hinge regions that lack the uroplakin complexes. As the bladder fills with urine, the discoidal vesicles are mobilized from the cytosol to add membrane and uroplakins to the lumenal surface of the bladder (54). When the bladder is emptied, excess uroplakin plaques are internalized and degraded through a process referred to as compensatory endocytosis (55).…”
Section: Mechanisms Of Bladder Cell Invasion By Upecmentioning
confidence: 99%
“…This membrane can be derived from various sources, including endosomal compartments, lysosomes, or, in the case of bladder umbrella cells, discoid vesicles. The delivery of membrane to sites of UPEC entry involves small GTP-binding proteins like Rab27b, which can also influence the intracellular trafficking and efflux of uroplakin plaques and UPEC alike (54, 8991). The silencing of Rab27b expression inhibits UPEC entry into host cells, and internalized UPEC initially localize within Rab27b-positive compartments (82, 89).…”
Section: Mechanisms Of Bladder Cell Invasion By Upecmentioning
confidence: 99%
“…Superficial urothelial cells contain unique cytoplasmic organelles including fusiform vesicles, which deliver preassembled UPK (uroplakin) proteins to the apical cell surface during bladder filling. Recent studies have demonstrated that specific small RAB GTPases (RAB27B and RAB11A) are highly enriched in superficial urothelial cells and are important for vesicle trafficking, UPK recycling [23][24][25][26][27][28], and exosome-mediated expulsion of intracellular UPEC [29][30][31]. Interestingly, network mapping of autophagy pathways has identified a Golgi-resident small GTPase, RAB33B, which interacts directly with ATG16L1 and thereby modulates autophagosome formation [32].…”
Section: Introductionmentioning
confidence: 99%